Histología y ultra estructura del testículo del charal Chirostoma jordani (Osteichthyes: Atherinidae) - Cardenas Reygadas, Rodolfo (1998)
Histological characteristics and garuetogenesis have received Iittle attention in endemic Mexican fish, thus they are little understood. In this study, the histology of the testis'of charal Chirosloma jordani, and ultrastruclure of gamete cells through fotonic and electron microscopy are described. Sixty male fish were collected in Corrales, Hidalgo state, México, 70 km NW México city. Charal testis are paíred, and added to the dorsolateral wall of abdomen. They are covered by a mesorquium, which has small black pigmentation spots. Testes are tubular, and spermatogonia are restricted lo Ihe distal part of tubules, basically in the cortical region. Cell sizes were measured: spermatogonia (8 ± 0.7 J-Im), primary spermatocytes (6.2 ± 0.3 11m), secondary spermatocytes (4.4 ± 0.1 *m), spermatids (2.5 ± 0.2 J-Im) and sperrnatozoa (15.4 ± 0.3 11m). Sertoli cells surround gamete cells; together they form cysts which have approximately the sarue degree of development. AH the testes have gamete cells simultaneously, and Leydig cells are easy lo see in the central patt of the testis.